IDENTIFIKASI POLA PEMANFAATAN RUANG UNTUK AKOMODASI PENGINAPAN PADA LAHAN HUNIAN MASYARAKAT DI LINGKUNGAN PERMUKIMAN DESA PELIATAN UBUD - I PUTU HARTAWAN; NI KADEK TANIA UTAMI PUTRI; NI KADEK SISKHA PRADNYAMINGRUM (GANEC SWARA, 2024)
Homestay within residential homes has become increasingly popular among foreign tourists recently. Due to the high demand for this type of accommodation, homestays and guesthouses have begun to emerge within the homes of local residents around Ubud. Houses that were originally intended solely as residences are now undergoing a functional transformation, adding a role as accommodations for tourists. This has created a complexity in spatial needs within one area, ultimately affecting and blending the spatial values traditionally held by the local community. If this trend continues without efforts to harmonize it with local cultural values and architecture, the cultural identity in the spatial patterns and values of traditional residences could fade. The researcher will examine in detail how space utilization patterns for accommodations within Ubud residences are being managed. Further, factors influencing the placement of spaces for lodging buildings will be explored. The results of the study indicate that most space utilization patterns for homestay buildings within residential homes in the village of Peliatan still apply local architectural styles, although there are some adjustments in construction systems and materials used.